UJI Escherichia coli PADA JAJANAN BAKSO BAKAR DI SEKOLAH KECAMATAN TAMPAN KOTA PEKANBARU DAN POTENSINYA SEBAGAI RANCANGAN LEMBAR KERJA SISWA PADA PEMBELAJARAN BIOLOGI DI SMA - Shintia Oktaviani; Irda Sayuti; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the presence of the bacteria Escherichia coli on grilled meatball snacks in schools of all Tampan districts in Pekanbaru city in April-May 2016. This research is an descriptive study was conducted with the 2 phases i.e. phase test the bacteria Escherichia coli in the lab and phase student worksheets design. The samples are taken by random purposive sampling method are purchased from 15 traders in different schools is soul around Tampan districts Pekanbaru city based on criteria that assigned and using the method Most Probable Number (MPN) with three stages of the test which consists of presumtive test, confirmative test and complete test using different growing media and incubated at 37oC temperature during 2x24 hours. The results obtained that from 15 samples examined obtained 11 samples contaminated by Escherichia coli. Research results are then used as material enrichment on teaching biology in senior high school class X on the Eubacteria material in the form of a student worksheets design.Key words: Escherichia coli, Grilled Meatball, Student Worksheet Design.